2018
DOI: 10.1051/e3sconf/20184400007
|View full text |Cite
|
Sign up to set email alerts
|

BTEX compounds identification by means of gas sensors arrays

Abstract: BTEX compounds can cause a threat to environment and human health. For this reason measurement devices are needed for rapid identification of such pollutants. The paper presents the results of recognition of mixtures of benzene, toluene, ethylbenzene and xylenes in humid air by means of two gas sensor arrays and linear discriminant analysis. Measurements were conducted during stabilization/solidification processes of contaminated soils. High classification ratios were obtained for both arrays (I: 88%-94%; II: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In [264], Badura et al have demonstrated the possibility of identifying BTEX-group compounds (i.e., benzene, toluene, ethylbenzene, and xylenes) in contaminated soils using a near real-time monitoring system based on two sensing arrays, each composed of 17 semiconductor Taguchi Gas Sensors (Figaro Engineering Inc., Arlington Heights, IL, USA) and a pattern recognition technique. High classification ratios were obtained for both gas sensor arrays (array I: 88-94%; array II: 94-96% of properly classified samples).…”
Section: Multicomponent Soil Analysis With Gas Sensor Arraysmentioning
confidence: 99%
“…In [264], Badura et al have demonstrated the possibility of identifying BTEX-group compounds (i.e., benzene, toluene, ethylbenzene, and xylenes) in contaminated soils using a near real-time monitoring system based on two sensing arrays, each composed of 17 semiconductor Taguchi Gas Sensors (Figaro Engineering Inc., Arlington Heights, IL, USA) and a pattern recognition technique. High classification ratios were obtained for both gas sensor arrays (array I: 88-94%; array II: 94-96% of properly classified samples).…”
Section: Multicomponent Soil Analysis With Gas Sensor Arraysmentioning
confidence: 99%